Effects of Pituitary Surgery and High-Dose Cabergoline Therapy on Metabolic Profile in Patients With Prolactinoma Resistant to Conventional Cabergoline Treatment - Pirchio, Rosa; Auriemma, Renata S.; Solari, Domenico; Arnesi, Mauro; Pivonello, Claudia; Negri, Mariarosaria; de Angelis, Cristina; Cavallo, Luigi M.; Cappabianca, Paolo; Colao, Annamaria; Pivonello, Rosario (Frontiers in Endocrinology, 2021)
Objective: Control of prolactin excess is associated with the improvement in gluco-insulinemic and lipid profile. The current study aimed at investigating the effects of pituitary surgery and medical therapy with high dose cabergoline (≥2mg/week) on metabolic profile in patients with prolactinoma resistant to cabergoline conventional doses (<2mg/week). Design: thirty-four patients (22 men, 12 women, aged 33.9±12.5 years) with prolactinoma (4 microadenomas and 30 macroadenomas) were included in the present study. Among them 17 (50%) received pituitary surgery (Group 1) and 17 (50%) medical therapy with high dose cabergoline (Group 2). Methods: In the whole patient cohort, anthropometric (weight, BMI) and biochemical (fasting glucose and insulin, triglycerides, total, HDL and LDL-cholesterol, HOMA-IR, HOMA-β and ISI0) parameters were evaluated before and within 12 months after treatment. Results: In Group 1, prolactin (p=0.002), total cholesterol (p=0.012), and triglycerides (p=0.030) significantly decreased after pituitary surgery compared to the baseline. Prolactin significantly correlated with fasting glucose (r=0.056, p=0.025). In Group 2, fasting insulin (p=0.033), HOMA-β (p=0.011) and ISI0 (p=0.011) significantly improved compared to baseline. Postoperative cabergoline dose significantly correlated with Δfasting glucose (r=-0.556, p=0.039) and ΔLDL cholesterol (r=- 0.521, p=0.046), and was the best predictor of ΔLDL cholesterol (r2=0.59, p=0.002) in Group 1. Conclusions: the rapid decrease in PRL levels induced by PS might improve lipid metabolism, whereas HD-CAB might exert a beneficial impact on both insulin secretion and peripheral sensitivity, thus inducing a global metabolic improvement.